(untitled) (Boston, 2005)
Human Sexuality: Diversity in Contemporary America is a pioneering text in many ways. The first text to achieve a full integration of cutting-edge research with a contemporary "sex-positive" approach, it also strives to represent the modern, diverse world that students encounter outside the classroom. Both within the text itself and throughout the exemplary art and photo program, the focus is on inclusion. Written by a leading sexuality researcher and experienced teachers of the human sexuality course, Human Sexuality has been lauded by students and instructors alike for providing the most integrated and non-judgmental view of sexual orientation available. This modern theme, along with the thorough coverage of sexuality and the media, engaging writing style, and biopsychosocial orientation, make the text a perennial best-seller. The new sixth edition builds on these strengths and adds updated information, a new design, and a highly crafted resource program to make the book more useful than ever.
Keywords: Sex,Sex customs,Hygiene, Sexual,Giới tính,Tập quán giới tính